(untitled) (Research, Society and Development, 2021)
Cassava (Manihot esculenta Crantz) is a crop of extreme economic and agronomic value because it has several varieties, it is highly nutritious and extremely important in the food industry in the generation of products for human consumption. The objective of the present study was to characterize the culture of cassava by means of its peculiarities, potential of the product called minimally processed cassava, to describe the methods used in the generation of this product to understand the dynamics of consumption of this product. Because it is a relatively easy crop and has low nutritional requirements, cassava is grown in most of the national territory, with a growing increase in production every year. The products generated from cassava are appreciated and sold in the national and international territory, the minimally processed cassava is among the products generated by this culture, of great economic value and of great acceptance in the consumer market. The work was carried out by means of a bibliographic survey that address relevant issues about cassava and generated products, mainly minimally processed table cassava to provide an assembled and relevant knowledge to the scientific community in agri-food technologies.